(3GdcTa hGdHjGf ef JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s ((3eOjfI Gdajhe ef CYeGd GdOjGQ GdeUQjI s)
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdbjGeI s
(3BNQgG (B:s
(3jfJgi HBNQ GdbQBf GdcQje hBNQ eG ajg (B: (3bGd YHO Gddg Hf YeQh (B: (3Ef GdQbi hGdJeGe hGdJhdI TQc EfeG jcajc Cf Jbhd GPgH GdHGS QH GdfGS dG TaGA EdG TaGDc GTa TaGA dG jZGOQ SbekG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs